Zeletice Group: Very low-grade Palaeozoic sequence at the base of Moravicum, Czech Republic - Leichmann,J.; Kapinus,A.; Pivnicka,L.; Weber,R. (Journal of the Czech Geological Society, 2006)
We define a new very low-grade metamorphic unit - Zeletice Group - that crops out in the northern termination of the Moravian Dyje window and in the central part of the Svratka window in the hanging wall of the Devonian Lazanky-Heroltice limestones and below the biotite-bearing phylites of the Pemegg-Upper Lukov-Bily Potok Groups. A part of the Zeletice Group in the Dyje window was earlier called Porphyroid Group (Preclik 1926b). The newly defined unit consists of greywackes, slates, metatuffites and sericite-chlorite-bearing marbles. This unit was so far considered as a lower part of the Pemegg-Upper Lukov-Bily Potok Groups. However, Zeletice Group differs from the overlying complexes by different lithology and considerably lower metamorphic overprinting. Pebbles of Devonian Lazanky-Heroltice limestones found in the metagreywackes define the lower age limit as Devonian. The age of cooling of the whole Moravian nappe pile c. 330-325 Ma ago (Dallmeyer et al. 1994) implies the minimum age of this Group. Our data indicate that an important Palaeozoic sequence overlays the Brunovistulian basement, apart of well-known Devonian limestones and siliciclastics, prior its collision with the Moravicum and Moldanubicum.
Keywords: Moravicum; Zeletice Group; marbles; metapelites; low-grade metamorphism; Bohemian Massif